AN ASSESSMENT OF ECONOMIC STATUS OF THE DAIRY FARMERS IN INDORE DISTRICT - Gunjan Upadhyay, Dr. Pratima Bais & Dr. Anil Chaudhary (International Journal of Research Science and Management, 2018)
This research was conducted in the Indore district of Madhya Pradesh to assess the economic status of the dairy farmers of the district. Personal interviews were conducted among 120 dairy farmers of all the four blocks of Indore district. Research shows that dairy farming is a profitable business but more profit can be made if one can take the member of cooperative society as he can get various benefits like better prices, improved veterinary services and easy credit facilities. Dairy farming hence, is proved as a good source of income and can be seen as a way to alleviate poverty and unemployment. It is also very useful for the womens as they can made extra income for household expenditure purpose which improves the economic status of their house and standard of living. Various suggestions has been given to the government and cooperative societies related to training of dairy farmers, market development and facilities need to be provided to the farmers for dairy development as dairy farmers were facing constraints related to market, prices and technology which helps them for better operations and motivates others to become the part of dairy industry.